Wildfire and spruce beetle outbreak have mixed effects on below‐canopy temperatures in a Rocky Mountain subalpine forest. (21st October 2020) - Carlson, Amanda R.; Sibold, Jason S.; Negrón, José F.
Abstract: Aim: Fine‐scale topography and canopy cover can play an important role in mediating effects of regional‐scale climate change on the below‐canopy environment in mountain forests. The aim of this study was to determine how below‐canopy temperatures in a high‐elevation Rocky Mountain forest have been affected by canopy change resulting from severe wildfire and spruce beetle outbreak within the last 10–15 years. Location: Eastern San Juan Mountains, Colorado, USA. Taxon: Picea engelmannii, Abies lasiocarpa, Dendroctonus rufipennis . Methods: We used a network of sensors to record temperatures for a full year in burned and beetle‐impacted areas. Using a Bayesian model that accounted for spatial structure in temperatures, we derived covariate parameters to determine the relative influence of topographic variables (elevation, aspect, slope, topographic position and solar radiation), live tree basal area and burned/unburned status on average daily maximum and minimum temperatures (Tmax, Tmin) in summer and winter. Results: Model parameters indicated that burned areas were warmer than unburned forest, with three of four average temperature variables (summer Tmax, winter Tmax, and winter Tmin) having >95% likelihood of a positive temperature difference in burned versus unburned locations. Mean temperature changes for these variables ranged from 0.41 to 0.74°C. Conversely, canopy loss in unburned, beetle‐killed forests did not meaningfully affect Tmax but resulted in slight cooling of Tmin. Modelled temperature changes resulting from 100% overstorey mortality were −1.29°C for summer Tmin (95% credible interval: −0.027 to −2.56°C) and −1.31°C for winter Tmin (95% credible interval: 0.17 to −2.79°C). Main Conclusions: Our results indicate that severe wildfire may exacerbate effects of climate change and increase the probability of ecosystem transitions. However, the effects of bark beetle outbreaks are more complex. Cooling of overnight minimum temperatures may counteract warming trends, but an increase in diurnal temperature ranges may have uncertain ecological consequences.